2016
DOI: 10.1007/s15010-016-0917-8
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of tick-borne encephalitis associated with raw goat milk and cheese consumption, Croatia, 2015

Abstract: The aim of this report is to emphasize the risk of acquiring TBE by the consumption of raw milk and dairy products. In April-May 2015, we registered the first outbreak of tick-borne encephalitis in Croatia in seven members out of ten exposed persons who consumed raw goat milk or cheese from the same supplier. Infection was confirmed by TBEV enzyme-linked immunosorbent assay (ELISA) in all patients. None had been vaccinated nor had observed a tick bite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 9 publications
1
32
0
6
Order By: Relevance
“…Based on the results of the epidemiological investigation, in the majority of cases TBE virus was transmitted by raw (unpasteurized) goat's milk/cheese (6,8,10,14,15). The question is whether the goats have more intense viraemia, longer lasting viraemia or merely goat's milk/cheese is more often consumed raw due to the belief that it is "healthier" this way (14). Fewer authors have reported the occurrence of TBEV in milk and/or cheese from sheep and cows (6)(7)(8)10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of the epidemiological investigation, in the majority of cases TBE virus was transmitted by raw (unpasteurized) goat's milk/cheese (6,8,10,14,15). The question is whether the goats have more intense viraemia, longer lasting viraemia or merely goat's milk/cheese is more often consumed raw due to the belief that it is "healthier" this way (14). Fewer authors have reported the occurrence of TBEV in milk and/or cheese from sheep and cows (6)(7)(8)10).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors indicate in their works the transmission of TBE by food (5,6,8,10,14,15). Kríz et al between 1997 and 2008 recorded 64 cases of TBE in patients who reported consumption of unpasteurized goat's milk (36 patients, 56.3%) or cheese from unpasteurized sheep's milk (21 patients, 32.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBEV is usually transmitted to humans via bites from infected ticks. However, oral transmission from the consumption of unpasteurised dairy products, the socalled alimentary route, has also been reported [13][14][15][16][17][18][19][20][21]. In these studies, the source of TBEV transmission was primarily either unpasteurised goat milk or cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Tick-borne encephalitis virus (TBEV) is one of the most frequent causes of the central nervous system infections in Europe, especially in endemic areas of Central and Eastern Europe and Russia (1,2). The epidemiology of TBE depends on various factors, such as increased recreational activities in areas infested by ticks, and climatic changes affecting tick habitats and in addition, anthropomorphic changes in agriculture and outdoor and free-time activities, increase the risk that humans will be infected TBE (2,6).…”
Section: Introductionmentioning
confidence: 99%